2020
DOI: 10.1002/14651858.cd012867.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic arterial embolization for the treatment of lower urinary tract symptoms in men with benign prostatic hyperplasia

Abstract: Prostatic arterial embolization for the treatment of lower urinary tract symptoms in men with benign prostatic hyperplasia. Cochrane database of systematic reviews (Online). https://www.cochrane.org/CD012867/PROSTATE_prostatic-arterial-embolization-treatment-lower-urinary-tractsymptoms-men-benign-prostatic Published in: Cochrane database of systematic reviews (Online)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 95 publications
0
24
0
5
Order By: Relevance
“…Importantly, PAE may reduce postprocedural ejaculatory dysfunction, although few data on erectile dysfunction are available [ 7 , 29 ]. After longer follow-ups, QoL appears similar with TURP and PAE, but the need for reintervention may be higher with PAE [ 30 ]. PAE might be a valuable alternative for the treatment of BPH-related LUTSs in selected patients in whom the symptoms are the main reason for considering surgery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PAE may reduce postprocedural ejaculatory dysfunction, although few data on erectile dysfunction are available [ 7 , 29 ]. After longer follow-ups, QoL appears similar with TURP and PAE, but the need for reintervention may be higher with PAE [ 30 ]. PAE might be a valuable alternative for the treatment of BPH-related LUTSs in selected patients in whom the symptoms are the main reason for considering surgery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We updated the methods of this review based on the protocol of a suite of reviews on minimally invasive treatments for LUTS [ 7 8 9 ]. We included parallel-group RCTs regardless of their publication status or language.…”
Section: Methodsmentioning
confidence: 99%
“…Some alternatives to TURP include laser enucleation, vaporisation, and Aquablation, but they all require spinal anaesthesia [ 2 ]. In recent years, the number of men undergoing TURP has steadily declined due to increasing pharmacologic treatments (alpha-blockers and 5-alpha-reductase inhibitors) and minimally-invasive treatments that are usually performed under local anaesthesia [ 6 ], such as convective radiofrequency water vapour therapy [ 7 ], prostatic urethral lift [ 8 ], prostatic arterial embolisation [ 9 ] which are covered in current evidence-based guidelines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 meta-analysis compared PAE and TURP by assessing four studies, all of which had a follow-up time period of at least 12 months. 2 This study therefore also used a 12-month time horizon where the outcomes of PAE and TURP were observed at 12 months post intervention. This is in line with the original UK-ROPE Study which also aimed to assess outcomes at 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…There have been multiple studies that have demonstrated the clinical effectiveness of PAE versus transurethral resection of the prostate (TURP), with significant improvements in symptoms, as measured by the International Prostatic Symptom Score (IPSS) reduction. 2 3 However, there are limited data on the cost utility of TURP compared with PAE.…”
Section: Introductionmentioning
confidence: 99%